Reconstruction of Severely Atrophic Pre-Maxilla Using Rhbmp-2 and Titanium Mesh for Dental Implants: A Case Report. - Fortes Ferreira, Cimara; da Escóssia, Jório; Pessoa Tabosa e Silva, Tércio; Luiz Zétola, André; Nunes Tavares, Rodrygo (Journal of Dentistry And Oral Implants, 2015)
This case report details reconstruction of a severely atrophic pre‑maxilla using rhBMP‑2 and a titanium mesh framework. Surgical technique, graft outcomes, and implant rehabilitation are described, with notes on indications and complications.
Keywords: Bone graft; dental implants; bone morphogenetic protein; atrophic